2019
DOI: 10.3390/nano10010055
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Process Parameters for a Chemi-Absorbed Graphene Coating and Its Nano Tribological Investigation

Abstract: A reduced graphene oxide coating was deposited on a titanium substrate for potential anti-friction applications in nano- or micro-mechanical systems. A γ-aminopropyltriethoxysilane coating was self-assembled on the substrate as an adhesive interlayer beforehand. The process parameters of self-assembly and hydrothermal reduction of graphene oxide coating were explored via water contact angle and tribological tests. Insufficient self-assembly duration of graphene oxide layer can be detected by water contact angl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…It was proposed that temperatures between 120 C and 180 C can be an effective reaction temperature for the fabrication of graphene coating. 79 External factors can also influence the corrosion behavior of coating as coating deposited on the metal surface can contain some inhomogeneity that can appear on the coating in form of cracks, microvoids, contaminants, etc. It was demonstrated that each of the factors can affect the integrity of the coating and influence the transport of aggressive species through the coating and the coating-substrate interface, thereby affecting the degradation process of the coating.…”
Section: Fabrication Parameter For Graphene Coatingmentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed that temperatures between 120 C and 180 C can be an effective reaction temperature for the fabrication of graphene coating. 79 External factors can also influence the corrosion behavior of coating as coating deposited on the metal surface can contain some inhomogeneity that can appear on the coating in form of cracks, microvoids, contaminants, etc. It was demonstrated that each of the factors can affect the integrity of the coating and influence the transport of aggressive species through the coating and the coating-substrate interface, thereby affecting the degradation process of the coating.…”
Section: Fabrication Parameter For Graphene Coatingmentioning
confidence: 99%
“…It was demonstrated that each of the factors can affect the integrity of the coating and influence the transport of aggressive species through the coating and the coating-substrate interface, thereby affecting the degradation process of the coating. 79 Controlling the parameter can enhance the quality and efficiency of the produced graphene coating as well as improve its corrosion resistance. Optimizing the CVD process parameter is another attempt explored to improve the performance of the graphene coating since variation in the process parameters can influence defect density of the graphene and affect the coating corrosion resistance.…”
Section: Fabrication Parameter For Graphene Coatingmentioning
confidence: 99%
“…The Raman results are obtained by detecting both inside and outside of the wear marks, as shown in Figure 14. It is generally believed that the characteristic peak of graphene exists the D peak at 1350 cm -1 and the G peak at 1580 cm -1 [46][47][48]. The diffraction peaks have been detected at 1350 cm -1 and 1580 cm -1 in both curves with a similar tendency.…”
Section: Chemical and Component Analysis Of The Contact Interfacementioning
confidence: 73%
“…PEALD can operate at lower temperatures than traditional thermal ALD, which is conducive to depositing unstable polymers at a high temperature. However, PEALD needs to provide the energy required for the reaction through plasma dissociation, which leads to damage of the substrate surface exposed to the environment of plasma discharge and high-energy electron bombardment ( Li P et al, 2019 ). REALD is similar to PEALD in that, it exposes the cultured substrate and film to free radicals and eliminates substrate exposure to high-energy ions and electron bombardment.…”
Section: Surface Modification Technologymentioning
confidence: 99%
“…Therefore, the design of the micro morphology of the implant surface may be able to promote the osteogenesis of the implant surface, inhibit the growth of bacteria and improve the wear resistance of the implant. In addition, LSE is well suitable for high temperature-resistant inorganic coating of materials (e.g., CaP, Si 3 N 4 , TiN-TiB, SiC) ( Das et al, 2014 ; Sahasrabudhe and Bandyopadhyay 2018 ; Li P et al, 2019 ; Zanocco et al, 2020 ). Niobium (Nb) is a costly refractory material with greater wear resistance and biocompatibility ( Zhang Y et al, 2015 ).…”
Section: Surface Modification Technologymentioning
confidence: 99%